MICROSOFT CLOUD SERVICES IN DISTANCE LEARNING SYSTEM “KHERSON VIRTUAL UNIVERSITY” (Journal of Information Technologies in Education (ITE), 2015)
E-learning with using spreadsheets requires the implementation of Excel-documents into the distance learning system. Simple and convenient solution of the problem of Excel-documents implementation is the use of cloud services.     Using cloud services, you can access to information resources of any level and any type with division of the rights of various groups of users to resources, using only an Internet connection and a Web browser.     Subject of research is the Microsoft cloud services.     The purpose of research is development and implementation of software module «ExcelReader» to use Excel spreadsheets on the Web pages of distance learning systems.     In this paper we solve the following tasks:     1) analyze the known software solutions to display Excel-documents in the WEB-based applications;     2) select an efficient software technology of processing Excel-documents;     3) design the access system and use of Web services of processing Excel-documents in distance learning system;     4) develop software module «ExcelReader» for correct display and edit Excel-documents on Web pages in distance learning;     5) implement software module «ExcelReader» in the distance learning system “Kherson Virtual University”.     Processes of creating, editing and implementation of MS Office documents into electronic resources of distance learning systems were modeled. In particular, the software module «ExcelReader» for usage Excel spreadsheets on Web pages of distance learning system “Kherson Virtual University” using "cloud" service Excel Web App from Microsoft was developed and implemented in the educational process.
Keywords: distance learning; e-learning; embedding; Excel; iCloud services; infrastructure; Kherson Virtual University